Larval fish assemblages in two nearshore areas of the Humboldt Current System during autumn-winter in northern Chile - Paredes, Lissette D.; Landaeta, Mauricio F.; González, M. Teresa (Revista de Biología Marina y Oceanografía, 2018)
This paper presents an analysis of spatial and temporal patterns in the fish larvae composition of two geographically adjacent nearshore areas within the Humboldt Current System (HCS), northern Chile. Five surveys were performed at Isla Santa María (ISM) and Punta Coloso (COL), Mejillones Peninsula. Ichthyoplankton were collected every 15 days in 2014 during the austral autumn-winter (May to August). A total of 412,410 fish larvae belonging to 36 taxa were identified, a high abundance compared with other HCS regions. Data also revealed similarities in species recorded compared with central Chile as well as differences compared with central Peru; a number of families were shared between these HCS regions and other systems (e.g., Canarias Current System). ISM was dominated by intertidal-subtidal species (e.g., Helcogrammoides cunninghami), while Engraulis ringens was most abundant at COL. Several species were positively correlated with dissolved oxygen (e.g., Auchenionchus microcirrhis), as well as temperature and Ekman transport (e.g., Sebastes oculatus), while the presence of others is negatively related to the same environmental parameters (e.g., Graus nigra). Results suggest that larvae differently utilize these two areas as a refuge or for feeding, and that adults might be coupling their spawning periods with short-term oceanographic features. Larval fish assemblages of nearshore areas in northern Chile are described here for the first time and highlight the important role of these two areas in the early developmental stages of fish species.